The Problem of Paradox and its Manifestations: A Study in the Titles of Najm Wali's Novels (Journal of the College of Education for Women, 2023)
The irony pushes us to inquire about what is in the text of contradiction, irony, suspense, and other acts of paradox, as well as a departure from what is logical, or familiar, that attracts the attention of the addressee, and this is what drives us to introspect the text and interrogate it in order to get to know the intended product of the text or its real or metaphorical intent. On the other hand, the irony is more in the literary text than in the scientific texts. Therefore, critics add the word literature to it in their definition. As it is represented by the paradox, we will seek to study the paradox of the title and the problematic that it may pose as the beginning of the text, and it expresses to us what is in the title of semantic overlap and existential contradiction or implicit (non-declared) with the main text or even a reference to it. From this point of view, we note that Najm Wali, as one of the most prominent Iraqi novelists who seeks to present a different and heterogeneous literature and benefits from the feature _Grebe_, especially the paradox, used titles for his novels that bear the characteristic of his paradoxes in most of them. In this study, we aim to analyze what is in these titles of irony in all its forms, based on the descriptive analytical approach. Through the following two axes:A: The theoretical dimension: This is an affirmation of what is related to the literary paradox, the paradox of the title, and the star of Wali in terms of definition, definition, and analysis.B: The logical dimension: This is concerned with applying literary irony to Najm Wali’s titles, such as: “The Hill of Lahm,” “The War in the Tarab Neighborhood,” “The Picture of Joseph,” and “A Place Called Kumait.” One of the results obtained by this study is that Najm Wali used the technique of title paradox, as a desire to draw the attention of the recipient to what is going on in his Iraqi society from the bitter reality, and on the other hand, he tried to reconcile the title and the cover, and to employ irony in all its forms with the main text for the same goal as well.